2004
DOI: 10.1017/s0031182004006225
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the anthelmintic effect of natural plant cysteine proteinases against the gastrointestinal nematode,Heligmosomoides polygyrus,in vitro

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. We examined the mechanism of action and compared the anthelmintic efficacy of cysteine proteinases from papaya, pineapple, fig, kiwi fruit and Egyptian milkweed in vitro using the rodent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
116
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 27 publications
(30 reference statements)
14
116
1
2
Order By: Relevance
“…2A-C, papaya latex, fig latex and pineapple fruit extract (containing active cysteine proteinases) caused progressive damage to the cuticle, beginning with the appearance of transverse wrinkles, followed by blistering and, finally, less localized cuticle digestion with expulsion of the worm intestine and other internal structures from points along the worm surface. Although these enzymes displayed a similar effect with T. muris to that previously documented with H. polygyrus (Stepek et al 2005), the damage took slightly longer to occur.…”
Section: Sem Of Worms Incubated With Plant Cysteine Proteinasessupporting
confidence: 71%
See 3 more Smart Citations
“…2A-C, papaya latex, fig latex and pineapple fruit extract (containing active cysteine proteinases) caused progressive damage to the cuticle, beginning with the appearance of transverse wrinkles, followed by blistering and, finally, less localized cuticle digestion with expulsion of the worm intestine and other internal structures from points along the worm surface. Although these enzymes displayed a similar effect with T. muris to that previously documented with H. polygyrus (Stepek et al 2005), the damage took slightly longer to occur.…”
Section: Sem Of Worms Incubated With Plant Cysteine Proteinasessupporting
confidence: 71%
“…This study has demonstrated conclusively that the anthelmintic efficacy of various plant cysteine proteinases observed in our previous study with Heligmosomoides polygyrus (Stepek et al 2005) is not species-specific, as these enzymes are comparably effective against the adult worms of Trichuris muris, a parasite that occupies the large intestine, predominantly living in the mouse caecum. Adult worms of this species were affected during in vitro incubation in the presence of most of the plant cysteine proteinases tested.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, to our knowledge, the current study is the first (i) to establish, unequivocally, that it is upon the cysteine proteinases present in the latex that the anthelmintic efficacy of papaya latex depends, and (ii) to provide evidence that the mechanisms of action in vivo and in vitro are essentially indistinguishable. In vitro studies (Stepek et al 2005(Stepek et al , 2006(Stepek et al , 2007 have demonstrated that cysteine proteinases attack the protective cuticle of the nematode, rapidly leading to complete dissolution of the parasite, a mechanism of action that differs from all the current anthelmintic drugs (Sangster and Gill, 1999 ;Martin and Robertson, 2000). This effect was similar to that described previously for 3 other gastrointestinal nematodes, H. polygyrus (Stepek et al 2005), T. muris (Stepek et al 2006) and Ascaris suum (Robbins, 1930 ;Berger and Asenjo, 1939), indicating that plant cysteine proteinases have a broad spectrum of activity against GI nematodes in vitro.…”
Section: Discussionmentioning
confidence: 99%